Acute Effects of Hip Mobility Exercises in Addition to Dynamic Warm-up on Vertical Jump, Maximal and Isometric Strength Parameters - Murat Can Çeken; Onat Çetin; Malik Beyleroğlu; Barbaros Demirtaş; Onur Çakır (Türk Spor ve Egzersiz Dergisi)
Abstract The aim of this study is to investigate the acute effects of hip mobility exercises applied before anaerobic activities on vertical jump, 1 repetition maximum (1TM) and isometric strength performances. For this purpose, 12 male athletes with a high level of training (age = 21 ± 1.2 years; height = 180 ± 0.05 m; body weight = 88.08 ± 9.17 kg) voluntarily participated in the study. Before starting the study, an approval report was obtained from the Sakarya University of Applied Sciences Ethics Committee and all athletes signed a voluntary consent form before the study. All participants were asked to perform a standard 15-minute dynamic warm-up procedure (dynamic stretching exercises related to cycling and tests) on the first measurement day, and then, in order to avoid fatigue in the athletes, 1 TM ( 1 Repetition Maximum) strength tests were applied. On the second measurement day, the subjects performed 8 different hip mobility exercises (2 sets x 20 seconds for each exercise) with the same 15-minute dynamic warm-up protocol and re-applied the tests applied on the first measurement day. When the findings were examined, it was found that there was no significant difference in the 1TM strength values of the deadlift exercise in the 1st and 2nd measurement sessions (p = 0.596 ). However, a significant difference was found between the 1TM strength, Isometric back-leg strength, Counter Movement Jump (CMJ) and Squat Jump (SJ) values of the squat exercise (p = 0.003, p = 0.002, p = 0.002, p = 0.002). In conclusion, this study shows that a dynamic warm-up protocol that includes hip mobility has a positive effect on vertical jump, maximal and isometric strength parameters.